Sedimentary Anthropogenic Carbon Signals From the Western Pacific Margin for the Last Century - Lee, Jay; Yang, Rick J.; Lin, Hui-Ling; Chen, Yi-Chi; Cai-Li, Ren-Yi; Ren, Haojia; Liu, James T. (Frontiers in Earth Science, 2022)
The declining trend of the global δ13C over the last century was about -0.01‰yr-1, according to global coral records. The decrease is attributable to the significant input of anthropogenic CO2 (13C Suess effect) to the atmosphere. Previous studies of δ13C in corals suggested that signals of the anthropogenic carbon in the Pacific and Indian Oceans are weaker than those in the Atlantic Ocean. However, biases relating to environments in which corals grow caused concerns. To investigate the record of anthropogenic carbon signals in the Western Pacific, a suite of 13 short box cores with good age-control were obtained from the continental slope off southwestern Taiwan through the FATES Program between 2004 and 2006. δ18O values of the planktonic foraminifera in collected cores were relatively stable at -2.5 ‰ ~ -2 ‰ in the last century, but δ13C values had a gradual secular decline after 1900s. The decreasing trend of δ13C began to intensify after 1960s, and its rate was similar to that in the Atlantic. Similar declining trends of δ13C were also found in corals at regions where the human activity is high (Liuqiu) and low (Dongsha). The atmospheric and oceanic simulations suggest that anthropogenic carbons could be transported from Liuqiu to Dongsha through atmospheric circulations in the troposphere, instead of oceanic circulations. Our findings indicate that signals of the anthropogenic carbon in the Western Pacific was not weaker than that recorded in the Atlantic, and the nearshore sediment can supplement the lack of δ13C records in corals, which are deficient when the environment is not suitable to grow.